Ergonomic evaluation of assembly line work activity in the automotive industry: a case study - Raquel Ferreira Araruna de Carvalho; Márcio Alves Marçal (Exploration of Musculoskeletal Diseases)
The automotive industry is growing worldwide with new technologies and seeking maximum cost savings. This sector is essential for the economic development of the country, with modern industries that invest in technological innovations and control of the activities of the production process. With this, the workstations become increasingly dynamic and characterized in the logic of productivity. Therefore, this study aimed to evaluate the work activity of operators of an assembly line of automotive components, from the ergonomic analysis. Through a descriptive and exploratory field study, the work activity of 30 operators of an assembly line of metallic components of the automotive industry was evaluated. Using instruments such as sociodemographic questionnaire; Nordic questionnaire; open interview, with collective questions about the development of the function, listed in an ergonomic demand items (EDIs) ranking; and complementary application of the NIOSH and OCRA methods. As a result, all respondents were male, with an average age of 30.13 ± 8.57 years, most had completed high school (76.7%), with an average working time in the company of almost two years (21.93 ± 12 months). Regarding relationships with coworkers, it was observed that the sector has a great relationship during the activities, with both colleagues and the boss. This study demonstrated a lower frequency of musculoskeletal symptoms in operators when compared to other studies. Symptoms that caused work leave were neck (3.3%), shoulders (3.3%), upper (6.7%) and lower back (6.7%), and hips/thighs (6.7%), ankle/foot (6.7%) were reported.